Responsiveness of Elite Cultivars vs. Ancestral Genotypes of Barley to Beneficial Rhizosphere Microbiome, Supporting Plant Defense Against Root-Lesion Nematodes - Elhady, Ahmed; Abbasi, Sakineh; Safaie, Naser; Heuer, Holger (Frontiers in Plant Science, 2021)
Harnessing plant-microbe interactions to advance crop resistance to pathogens could be a keystone in sustainable agriculture. The breeding of crops to maximize yield in intensive agriculture might have led to the loss of traits that are necessary for beneficial plant-soil feedback. In this study, we tested whether the soil microbiome can induce a stronger plant defense against root-lesion nematodes in ancestral genotypes of barley than in elite cultivars. Plants were grown in a sterile substrate with or without the inoculation of rhizosphere microbiomes, and Pratylenchus neglectus was inoculated to the roots. Unexpectedly, elite cultivars profited significantly more from the microbiome than ancestral genotypes, by the reduction of nematodes in roots and the increased shoot weight relative to control plants. The elite cultivars had higher microbial densities in the rhizosphere, which were correlated with root weight. The structure of the bacterial and fungal community of elite and ancestral genotypes differed, as compared by 16S rDNA or internal transcribed spacer amplicon profiles in denaturing gradient gel electrophoresis. The elite cultivars differed in responsiveness to the microbiome. For the most responsive cultivars Beysehir and Jolgeh, the strong microbe-induced suppression of nematodes coincided with the strongest microbe-dependent increase in transcripts of salicylic acid-regulated defense genes after nematode invasion, while the jasmonate-regulated genes LOX2 and AOS were downregulated in roots with the inoculated microbiome. The microbe-triggered modulation of defense gene expression differed significantly between elite and ancestral genotypes of barley. Soil microbiomes conditioned by maize roots suppressed the nematodes in elite cultivars, while the corresponding bulk soil microbiome did not. In conclusion, cultivars Beysehir and Jolgeh harbor the genetic background for a positive plant-microbiome feedback. Exploiting these traits in breeding for responsiveness to beneficial soil microbiomes, accompanied by soil biome management for compatible plant-microbe interactions, will support low-input agriculture and sustainability.